Transforming leaders to transform hospitals. Cultivating ethical leadership for compassionate healthcare - Ricci, Elena (Medicina e Morale, 2024)
The importance of compassionate care has been widely acknowledged in the literature as a crucial component for enhancing patient care, improving clinical outcomes, and reducing burnout, compassion fatigue, malpractice, and healthcare costs (Watts et al., 2023). However, many healthcare systems continue to struggle with effectively implementing and sustaining compassionate care practices due to the burden of administration, limitations in resources, and a focus on efficiency and profitability. The purpose of this paper is to advocate for the necessity of (re) "humanizing" the healthcare environment, which is urgently needed today to counteract the trend of eroding the value or essence of care practices by refocusing on the patient and their family. Specifically, this paper will argue that to reverse this trend, it is crucial to transform the education of healthcare facility leaders and managers at all levels. It is vital to provide them with guidelines and training that is not only technical but also ethical, with a focus on character education. This approach would enable them to recognize the right values and effectively address complex situations from a moral perspective. Providing leaders with the opportunity to flourish through dedicated programs can positively transform our hospitals and healthcare facilities. Such programs are essential for creating a balanced healthcare environment where efficiency and compassionate care coexist, leading to improved care outcomes, reduced costs, and enhanced well-being for professionals.